Interfacial Behavior of the Steel–UHPC Composite Deck With Toughened Epoxy Bonding - Chen, Jun; Leng, Jingchen; Jiang, Jinlong; Zou, Yang; Zhou, Jianting (Frontiers in Materials, 2022)
Using traditional stud connectors to connect the ultra-high-performance concrete layer and steel deck is detrimental to the construction speed and fatigue performance of the composite structure. Connecting the steel–UHPC interface with toughened epoxy bonding is a potential alternative to avoid this issue. To explore whether the toughened epoxy bonding interface can reduce the amount of bridge deck studs or even cancel the studs, a numerical simulation was conducted in this paper. The non-toughened epoxy bonding interface, the toughened epoxy bonding interface, a few studs + toughened epoxy bonding interface, and the full stud connection interface were designed to study the interfacial behavior of the steel–UHPC composite deck. Moreover, the constitutive model of the toughened epoxy bonding interface is verified through the direct shear test and compression-shear test. The results show that the maximum interface shear stress of the toughened epoxy bonding interface is 0.61 MPa under the standard wheel load, which is 20.78% lower than that of the non-toughened epoxy bonding interface. Under the overload, the interface failure of the toughened epoxy bonding interface is more concentrated and exhibits a smaller damage area compared with the non-toughened epoxy bonding interface. When the interface defect is 5%, the toughened epoxy bonding interface only has a few interface damages, exhibiting good defect tolerance. Compared to the traditional full stud connection interface, the interface shear stress in the few studs + toughened epoxy bonding interface is more uniform, which avoids the stress concentration in the root of studs, and the studs’ average stress is significantly reduced by 63.21%. It is verified that using the toughened epoxy bonding interface can significantly reduce the amount of studs.